The Politics of Criminal Law Behind the Mining Industry’s Image: Uncovering CSR Scandals in Indonesia - Basrawi Basrawi; M. Said Karim; Aminuddin Ilmar (Journal of Law and Legal Reform, 2025)
Corporate branding through Corporate Social Responsibility (CSR) programs has become a key strategy for many mining companies in Indonesia. CSR is supposed to be a tangible manifestation of a company’s contribution to social and environmental development around its area of operation. However, in practice, CSR is often just an image tool to improve the company’s reputation without having a significant positive impact on society. This article examines the phenomenon of CSR in the Indonesian mining sector, which is often involved in scandals and manipulative practices. The research highlights various cases where mining companies fail to fulfill their social responsibilities, manipulate CSR reports, and exploit local communities. Through a qualitative analysis approach, this article reveals that CSR programs in the mining sector are more often used as a means to improve public image than to make a real contribution to sustainable development. The conclusion of this study shows the need for supervisory reforms and clear rules related to criminal sanctions for misuse of CSR funds so that CSR implementation does not only become a means of imaging, but actually has a positive sustainable impact.